F-Prostaglandin receptor regulates endothelial cell function via fibroblast growth factor-2 - Keightley, Margaret C (BioMed Central, 2010)
BACKGROUND: Prostaglandin (PG) F(2α )is a key regulator of endometrial function and exerts its biological action after coupling with its heptahelical G protein-coupled receptor (FP receptor). In endometrial adenocarcinoma the FP receptor expression is elevated. We have shown previously that PGF(2α)-FP receptor signalling in endometrial adenocarcinoma cells can upregulate several angiogenic factors including fibroblast growth factor-2 (FGF2). In the present study, we investigated the paracrine effect of conditioned medium produced via PGF(2α)-FP receptor signalling in endometrial adenocarcinoma cells stably expressing the FP receptor (Ishikawa FPS cells), on endothelial cell function. RESULTS: Conditioned medium (CM) was collected from FPS cells after 24 hrs treatment with either vehicle (V CM) or 100 nM PGF(2α )(P CM). Treatment of human umbilical vein endothelial cells (HUVECs) with P CM significantly enhanced endothelial cell differentiation (network formation) and proliferation. Using chemical inhibitors of intracellular signalling, we found that P CM-stimulated endothelial cell network formation was mediated by secretion of endothelial PGF(2α )and activation of endothelial FP receptors, following FGF2-FGFR1 signalling, phosphorylation of ERK1/2 and induction of COX-2. Whereas, P CM stimulation of endothelial cell proliferation occurred independently of PGF(2α )secretion via an FGF2-FGFR1-ERK1/2 dependent mechanism involving activation of the mTOR pathway. CONCLUSIONS: Taken together, we have shown a novel mechanism whereby epithelial prostaglandin F(2α)-FP signalling regulates endothelial cell network formation and proliferation. In addition we provide novel in vitro evidence to suggest that prostaglandin F(2α )can directly regulate endothelial cell network formation but not endothelial cell proliferation. These findings have relevance for pathologies where the FP receptor is aberrantly expressed, such as endometrial adenocarcinoma, and provide in vitro evidence to suggest that targeting the FP receptor could provide an anti-angiogenic approach to reducing tumour vasculature and growth.